On the stationarity of current account deficits in the European union (2010)
In this paper, we test for the stationarity of EU current account deficits. Our testing strategy addresses two key concerns with regard to unit-root panel data testing, namely (i) the identification of which panel members are stationary, and (ii) the presence of cross-sectional dependence. For this purpose, we employ an AR-based bootstrap approach to the Hadri (2000) test. While there is only mixed evidence that current account stationarity applies when examining individual countries, this does not appear to be the case when considering panels comprising both EU and non-EU members. © 2010 Blackwell Publishing Ltd.